DEVELOPMENT IN RESEARCH ON THE MECHANICAL PROPERTY OF ADHESIVE JOINTS - WANG YuQi; HE XiaoCong; ZENG Kai (Jixie qiangdu)
The need to design lightweight structures and the increased use of lightweight materials in industrial field,has led to wide use of adhesive bonding. In order to improve the mechanical strength and reliability of adhesive joints,the research results of mechanical property of adhesive joints at home and abroad was summarized,including the static analysis,fatigue analysis and dynamic analysis. The problems and development trend of mechanical property of adhesive joints have been pointed out.